Scalar Implicature in Absence of Epistemic Reasoning? The Case of Autism Spectrum Disorder. Issue 3 (3rd July 2018) - Hochstein, Lara; Bale, Alan; Barner, David
ABSTRACT: We investigated "scalar implicature" in adolescents and children with autism spectrum disorder (ASD) to test whether theory of mind deficits associated with autism affect pragmatic inferences in language. We tested scalar implicature computation in adolescents with ASD (12–18 years) and asked whether they reason about mental states when computing inferences. Like previous studies, we found the adolescents with ASD computed implicatures to the same degree as neurotypical adults. However, we also found that this ability may not rely on epistemic reasoning. In a test of epistemic reasoning (which probed so-called "ignorance implicature") we found that adolescents with ASD were able to make epistemic inferences required by Gricean models of scalar implicature when they were explicitly required by the task to do so. However, in a second task, which asked whether subjects spontaneously reason about mental states in the service of scalar implicature when not explicitly asked to, we found that adolescents with ASD did not engage in epistemic reasoning, leading them to compute scalar implicatures in contexts in which they were not justified. Based on these data, we argue that epistemic reasoning may not be a core, constitutive component of scalar implicature.